tg3x+tg2x+tgx=0
X€(apartina)R
Rayzen:
sigur nu era -tg3x?
Răspunsuri la întrebare
Răspuns de
6
[tex]tgx+tg2x+tg3x=0 \Rightarrow tgx+tg2x+tg(x+2x) = 0 \Rightarrow \\ \\ \Rightarrow tgx+tg2x+ \dfrac{tgx+tg2x}{1-tgx\cdot tg2x} = 0 \Rightarrow \\ \\ \Rightarrow (tgx+tg2x)\cdot\Big(1+ \dfrac{1}{1-tgx\cdot tg2x}\Big)=0 \Rightarrow \\ \\ \Rightarrow (tgx+tg2x)\cdot\Big( \dfrac{1-tgx\cdot tg 2x+1}{1-tgx\cdot tg2x}\Big) = 0 \Big|\cdot(1-tgx\cdot tg2x) \Rightarrow \\ \\ (tgx+tg2x)\cdot(2-tgx\cdot tg2x)=0 \\ \\ \boxed{1} \quad tgx+tg2x=0 \\ \\ $sau$ \\ \\ \boxed{2} \quad tgx\cdot tg2x=2
[/tex]
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Biologie,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă